Effect of Artificial Discontinuities Formed by Presplitting with Different Depths on Structural Damage Risk - Enver Alan (International Society of Explosives Engineers)
This Research & Development (R&D) study was conducted in the field of applied blasting engineering in Ethiopia, within the AKH Railway Project, which was built in Girena, within the boundaries of the province of Mersa, in the Basalt Quarry at km 346, Ashangi Formation, occured in Eocene geological time in the aphanitic trachibasalt. Under the scope of the study, which has been performed to determine the effects of the artificial discontinuities at different depths and the effects of artificial discontinuities through structural damage risk, three test areas, at the same location and same formation, were considered. Six numbers of artificial discontinuities, each 10 m (32, 81 ft) transverse, were created by using pre-splitting and drilling-blasting technology. The number of sequential artificial discontinuities on each test area is two and they have the same length. The length of artificial discontinuities are; 6,80 m (22,31 ft) at the first test area, 13,60 m (44,62 ft) at the second test area and 17,00 m (55,77 ft) at the third test area respectively. The distance between sequential artificial discontinuities is 8 m (26,25ft) on each test area. Thirty-one shots were executed in order to produce vibration (10 shots on the first test area, 11 shots on the second area, 10 shots on the third test area). One hundred and twenty-three seismic recordings were obtained during the execution of the shots by using 4 seismographs. The closest distance between the shot points and the nearest measuring station is 5,30 m (17,39 ft). During the shots, the rock was cracked and there was no fragmentation and/or fly rock. At the first test area, measured PPV values are between 25,40-127,00 mm/s (1-5 inch/s) before the first artificial discontinuity and less than 50,80 mm/s (2 inch/s) after the second artificial discontinuity. At the second test area, measured PPV values are between 76,20-177,80 mm/s (3-7 inch/s) before the first artificial discontinuity and less than 76,20 mm/s (3 inch/s) after the second artificial discontinuity. At the third test area, measured PPV values are between 50,80-279,40 mm/s (2-11 inch/s) before the first artificial discontinuity and less than 50,80 mm/s (2 inch/s) after the second artificial discontinuity. Peak reduction rates in Peak Particle Velocity (PPV) values determined by measuring as follows: In the first test area 95,77% (106,00 mm/s to 4,48 mm/s) (4,17 in/s to 0,18 in/s), in the second test area 79,77% (176,00 mm/s to 35,60 mm/s) (6,93 in/s to 1,40 in/s), in the third test area 95,85% (from 205,00 mm/s to 8,55 mm/s) (from 8,07 in/s to 0,34 in/s). The arithmetic mean of the differences of PPV values (decrease rate) is 82,66% in the first test area, 69,37% in the second test area, and 92,03% in the third test area. The highest sound value is 138,50 dB and is defined as “noise”. When the measured parameter values are examined it was determined on the USBM norm graphs that these vibrations carry a risk of structural damage in the region before the first artificial discontinuity. While passing through artificial discontinuities the vibrations progress by losing energy and the vibrations passing through two artificial discontinuities do not carry structural damage risk under current conditions.